Pediatric intracerebral anaplastic ganglioglioma : A Case Report - Shrestha, Dipendra Kumar; Rajbhandari, Binod; Pradhanang, Amit; Shilpakar, Sushil Krishna (Nepal Journal of Neuroscience, 2019)
Anaplastic ganglioglioma (AGG) is an extremely rare aggressive, epileptogenic braintumor. It is considered to be WHO grade III variant of ganglioglioma. Due to non-specific clinical manifestations and radiographic features, preoperative diagnosis of AGG may be very difficult at times. Frequently, it may be confused with either low grade ganglioglioma, dysembryoplastic neuroepithelial tumor (DNET) or high grade primary glial tumors. Here, were port a young girl presenting with headache and seizures preliminarily diagnosed as DNET but histopathologically proven as an aplastic ganglioglioma, along with a brief literature review.